2013
DOI: 10.1002/tox.21875
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of cytochrome P450scc as an initial adverse effect of adult exposure to diethylstilbestrol on testicular steroidogenesis

Abstract: Reproductive toxicities and endocrine disruptions caused by chemicals in adult males are still poorly understood. It is our objectives to understand further details of the initial adverse effects leading severe testicular toxicities of a pharmaceutical endocrine disruptor, diethylstilbestrol (DES). Downregulations of both testicular regulatory proteins, such as the steroidogenic acute regulatory protein (StAR) and the peripheral benzodiazepine receptor (PBR), which play important roles in the transport of chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…The mechanism by which adrenal cholesterol is decreased upon DES treatment remains unclear; however, DES was shown to disrupt the cholesterol supply for optimal corticosterone synthesis. The mechanism of DES toxicity in the adrenal glands appears to be distinct from that in the testis, as has been previously reported by us, in which DES influences the proteins associated with steroidogenesis (including P450scc (Maeda et al 2013b)) but does not disrupt cholesterol content of the testis (data not shown). Plasma lipoprotein deficiency in mice as a result of feeding with probucol is associated with decreased adrenal cortex cholesterol levels, a lower basal and stress-induced plasma glucocorticoid level (Hoekstra et al 2010).…”
Section: Figuresupporting
confidence: 55%
See 4 more Smart Citations
“…The mechanism by which adrenal cholesterol is decreased upon DES treatment remains unclear; however, DES was shown to disrupt the cholesterol supply for optimal corticosterone synthesis. The mechanism of DES toxicity in the adrenal glands appears to be distinct from that in the testis, as has been previously reported by us, in which DES influences the proteins associated with steroidogenesis (including P450scc (Maeda et al 2013b)) but does not disrupt cholesterol content of the testis (data not shown). Plasma lipoprotein deficiency in mice as a result of feeding with probucol is associated with decreased adrenal cortex cholesterol levels, a lower basal and stress-induced plasma glucocorticoid level (Hoekstra et al 2010).…”
Section: Figuresupporting
confidence: 55%
“…We found adverse effects on the testicular proteins at the lower dose (0.1 mg/rat every 2 days; Li et al 2011, Maeda et al 2013b. In this study, we found adrenal abnormalities only after 1 week of treatment with DES (0.1 mg/rat every 2 days), and revealed that the endocrine disruptor DES disrupts corticosteroid biosynthesis via cholesterol insufficiency.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations